CURRENT TRENDS IN THE TRANSFORMATION OF LAW (FROM TRADITIONAL TO DIGITAL LAW) - Утемуратов, Махмут (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article examines modern trends in the transformation of law from traditional to digital law, including the transition of society to the stage of artificial intelligence technologies, which implies the emergence of a new platform for law and order, which is usually referred to as digital or information technology. The views of scientists on artificial intelligence from a scientific point of view are also considered.